Phosphate-amidoxime synergistic functional cellulose adsorbent as well as preparation method and application thereof

By introducing phosphate groups and amylopectin groups onto cellulose, a phosphate-amylopectin synergistic functionalized cellulose adsorbent was prepared, which solved the problem of the unsatisfactory adsorption capacity of cellulose under acidic conditions, and achieved efficient adsorption and recycling, and was applied to the removal of uranium ions in acidic wastewater.

CN121669181APending Publication Date: 2026-03-17JINAN NURSING VOCATIONAL COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610006460.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-05
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing cellulose adsorbents have unsatisfactory adsorption capacity, poor adsorption effect, and poor cycle stability under acidic conditions, making them difficult to effectively treat acidic uranium-containing wastewater.

Method used

A phosphate-mercapto-oxime synergistic functionalized cellulose adsorbent was prepared by introducing phosphate and amercapto-oxime groups onto cellulose in a three-step reaction, thereby improving its uranium ion adsorption capacity under acidic conditions.

Benefits of technology

The uranium ion adsorption capacity of cellulose adsorbent was significantly improved under acidic conditions, enabling the recovery of uranium resources and solving the problem of uranium pollution. This also achieved efficient adsorption and recycling of uranium resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121669181A_ABST
    Figure CN121669181A_ABST
Patent Text Reader

Abstract

The invention provides a phosphate-amidoxime synergistic functional cellulose adsorbent as well as a preparation method and application thereof, and belongs to the field of sewage treatment and environmental protection. The preparation method comprises the following steps: firstly, enabling a nitrile compound to react with cellulose, and introducing cyano into the cellulose; then hydroxylamine compounds and alkali react with cyanoethyl cellulose to obtain amidoxime group modified cellulose, and finally phosphorylation reaction is performed to obtain the phosphate group-amidoxime group synergistic functional cellulose. The amidoxime group and the phosphate group are introduced into the cellulose through the three-step reaction, the reaction condition is mild, the process is controllable, the operation is simple, and large-scale production is easy to realize. The phosphate group-amidoxime group synergistic functional cellulose is prepared by the method provided by the invention, and amidoxime group and phosphate group in the prepared cellulose adsorbent are coordinated synergistically, so that the coordination capability of the adsorbent and uranium ions is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment and environmental protection technology, specifically relating to a phosphate-mercapto-oxime synergistic functionalized cellulose adsorbent, its preparation method, and its application. Background Technology

[0002] As a clean, efficient, and low-carbon energy form, nuclear energy is considered an important direction for future energy development. Uranium, a crucial fuel for nuclear energy, is currently primarily sourced from natural uranium mining. Global uranium mining mainly relies on acid leaching, generating large amounts of acidic radioactive wastewater with a pH of 4 or lower during the mining and smelting process. Excessive radioactive uranium in this wastewater not only wastes uranium resources but also threatens ecological and environmental security. Therefore, developing efficient uranium separation technologies to deeply purify acidic radioactive wastewater and promote the sustainable development of nuclear energy production is urgently needed. Scientists have researched various methods to address uranium contamination, including chemical precipitation, ion exchange, membrane separation, adsorption, and electrochemical methods. Among these, adsorption stands out due to its simple operation, high cost-effectiveness, and lack of secondary pollutant generation. Among numerous adsorption materials, biomass materials have attracted significant attention due to their low cost, renewability, and environmental degradability. However, biomass materials generally suffer from low adsorption capacity, poor selectivity, and difficulty in regeneration, necessitating the development of novel, highly efficient biomass adsorbents.

[0003] Cellulose, as the most abundant biomass resource on Earth, has attracted widespread attention in the development of uranium adsorbents due to its renewable and biodegradable nature. However, current cellulose-based adsorbents are mainly used for the removal of uranium from neutral wastewater. Under acidic conditions, problems such as unsatisfactory adsorption capacity, slow adsorption rate, and poor cycle stability still exist. Therefore, the development of cellulose adsorbents for treating acidic uranium-containing wastewater is of great significance. Summary of the Invention

[0004] The purpose of this invention is to provide a phosphate-based-mercapto-oxime synergistic functionalized cellulose adsorbent, its preparation method, and its application, effectively overcoming the shortcomings of existing technologies such as unsatisfactory adsorption capacity, poor adsorption effect, and poor cycle stability under acidic conditions.

[0005] To achieve the above or other objectives, the present invention is implemented through the following technical solutions.

[0006] A method for preparing a phosphate-aminooxime synergistic functionalized cellulose adsorbent includes the following steps: S1. Dissolve cellulose powder in an alkaline aqueous solution of urea, stir under an ice-water bath, then add nitrile compounds, react under nitrogen protection, adjust the pH after the reaction is complete, and then filter, wash and freeze dry to obtain cyanoethyl cellulose material; S2. Dissolve the cyanoethyl cellulose material obtained in S1 in an organic solvent, add hydroxylamine compounds and alkali metal hydroxides, and heat the reaction. After the reaction is complete, centrifuge to remove insoluble matter, add ethanol to the solution to form a precipitate, and obtain amylopectin-oxime cellulose by filtration, washing with ethanol, and freeze drying. S3, amylopyridine cellulose was dissolved in an organic solvent, and then a phosphorus-containing compound was added. The mixture was heated to react, and after the reaction was completed, it was cooled to room temperature, filtered, washed with water, and freeze-dried to obtain phosphate-amylopyridine co-functionalized cellulose.

[0007] Furthermore, the alkaline aqueous solution of urea in S1 refers to the addition of an alkaline compound to the urea aqueous solution; the alkaline compound can be sodium hydroxide or potassium hydroxide. The mass ratio of the alkaline compound, urea, and water is 1:(1~10):(1~50).

[0008] Furthermore, the nitrile compound is selected from one of acrylonitrile, methacrylonitrile, trans-butenedionitrile, cis-butenedionitrile, and 3-butenedionitrile.

[0009] Furthermore, in step S1, the mass ratio of cellulose powder to nitrile compound is 5:(1~10).

[0010] Furthermore, the mass concentration of cellulose in the alkaline aqueous solution of urea ranges from 1% to 50%.

[0011] Furthermore, in step S1, the reaction temperature is 0~30℃ and the reaction time is 8~20 hours.

[0012] Preferably, after the reaction in step S1 is completed, the pH of the reaction system is adjusted to 7.0 using acetic acid.

[0013] Furthermore, the organic solvent in step S2 is selected from one of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.

[0014] Furthermore, in step S2, the hydroxylamine compound is selected from hydroxylamine hydrochloride, hydroxylamine sulfate, O-methylhydroxylamine hydrochloride, and free hydroxylamine. The alkali metal hydroxide is sodium hydroxide or potassium hydroxide.

[0015] Furthermore, in step S2, the mass concentration of cyanoethyl cellulose material in the organic solvent ranges from 1% to 50%, and the mass ratio of cyanoethyl cellulose, hydroxylamine compounds, and alkali metal hydroxides is 2:(1~5):(1~10).

[0016] Furthermore, in step S2, the reaction temperature is 40~80℃ and the reaction time is 10~20 hours.

[0017] Further, in step S2, the amount of ethanol added is increased until no more precipitation occurs.

[0018] Furthermore, the organic solvent in step S3 is selected from one of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.

[0019] Furthermore, the phosphorus-containing compound in step S3 is selected from one of phosphorus pentoxide, phosphoric acid, polyphosphoric acid, and phosphorus oxychloride.

[0020] Furthermore, in step S3, the mass concentration of chloroquine oxime cellulose in the organic solvent ranges from 1% to 4%.

[0021] Furthermore, in step S3, the mass ratio of chloroquine oxime cellulose to phosphorus-containing compound is 2:(1~5).

[0022] Furthermore, in step S3, the reaction temperature is 80~120℃ and the reaction time is 1~5 hours.

[0023] A second aspect of this invention protects a phosphate-mercapto-oxime synergistic functionalized cellulose adsorbent prepared using the above-described preparation method.

[0024] The third aspect of this invention protects the application of the above-mentioned phosphate-mercapto-oxime synergistic functionalized cellulose adsorbent in the field of uranium adsorption and recovery from wastewater.

[0025] This invention introduces a metallo-oxime group and a phosphate group into cellulose through a three-step reaction. The reaction conditions are mild, the process is controllable, the operation is simple, and it is easy to achieve large-scale production. A phosphate-metallo-oxime synergistic functionalized cellulose was prepared using the method of this invention. In the prepared cellulose adsorbent, the metallo-oxime group and the phosphate group coordinate synergistically, greatly improving the adsorbent's ability to coordinate with uranium ions. It not only efficiently adsorbs uranium ions under neutral conditions but also exhibits excellent uranium adsorption capacity under acidic conditions, effectively improving the uranium ion adsorption capacity of cellulose under acidic conditions. It can be widely used for the removal of uranium ions from acidic wastewater, effectively solving the problem of uranium pollution and simultaneously realizing the recovery of uranium resources. Attached Figure Description

[0026] Figure 1 The image shows a SEM image of the phosphate-mercapto-oxime co-functionalized cellulose prepared in Example 1.

[0027] Figure 2 The infrared spectrum of the phosphate-mercapto-oxime co-functionalized cellulose prepared in Example 1 is shown.

[0028] Figure 3 The images show a comparison of the physical samples of the phosphate-mercapto-oxime synergistic functionalized cellulose prepared in Example 1 before and after adsorption of uranium ions.

[0029] Figure 4The graph shows the effect of adsorption time on the amount of uranium ions adsorbed in Application Example 1.

[0030] Figure 5 The graph shows the effect of solution pH on the amount of uranium ions adsorbed in Example 2.

[0031] Figure 6 This is a cyclic adsorption diagram of uranium ions by the adsorbent in Example 3.

[0032] Figure 7 The graph shows the effect of the adsorbent obtained from Comparative Example 1 on the adsorption capacity of uranium ions in Application Example 4.

[0033] Figure 8 The graph shows the effect of the adsorbent obtained from Comparative Example 2 on the amount of uranium ions adsorbed in Application Example 5. Detailed Implementation

[0034] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, unless otherwise specified, the following embodiments and features described therein can be combined with each other.

[0035] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" used in this specification are only for clarity of description and are not intended to limit the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered as part of the scope of the invention.

[0036] The technical solution of the present invention will be described in detail below through several specific embodiments. Unless otherwise stated, the raw materials and reagents used in the following embodiments are commercially available products, or can be prepared by conventional methods in the art. Unless otherwise specified, the detection methods used in the embodiments of the present invention are conventional detection methods in the industry.

[0037] In this embodiment of the invention, inductively coupled plasma atomic emission spectrometry (ICP-AES) is used to measure the ion concentration in the aqueous solution, and the adsorption capacity and removal rate are calculated using the following formulas:

[0038] In the formula, Q e —Equilibrium adsorption capacity (mg / g), C0—Ion concentration in the solution before adsorption (mg / L), C e —Ion concentration in the solution after adsorption (mg / L), V—Volume of the solution (L), m—Mass of the hydrogel (g), R—Removal rate.

[0039] Example 1

[0040] S1: 7.0 g sodium hydroxide and 12.0 g urea were dissolved in 100.0 g water. 5.0 g cellulose powder was added to the above solution. The mixture was stirred vigorously in an ice-water bath, and then 1.0 g acrylonitrile was slowly added. The reaction was carried out at 30°C for 8 hours under nitrogen protection. After the reaction was completed, acetic acid was added to adjust the pH to 7.0. The resulting white solid was filtered, washed, and freeze-dried to obtain cyanoethyl cellulose material.

[0041] S2: 2.0 g of cyanoethyl cellulose was dissolved in 80 g of N,N-dimethylformamide, and then 2.4 g of hydroxylamine hydrochloride and 1.4 g of sodium hydroxide were added. The mixture was heated at 65°C for 10 hours. After the reaction was completed, the insoluble matter was removed by centrifugation. Then, ethanol was added to the solution to form a precipitate. After filtration, washing with ethanol, and freeze drying, the amylopyroxycellulose was obtained.

[0042] S3: 2.0 g of amylopyridine cellulose was dissolved in 80 g of N,N-dimethylformamide, and then 1.0 g of phosphorus pentoxide powder was added. The mixture was heated at 90°C for 1 hour. After the reaction was completed, it was cooled to room temperature. The white solid was filtered, washed with water, and freeze-dried to obtain a phosphate-amylopyridine synergistic functionalized cellulose adsorbent.

[0043] The structure of the obtained adsorbent was characterized using SEM, and the results are as follows: Figure 1 As shown in the figure, the material exhibits a sheet-like structure. The obtained adsorbent was characterized using infrared spectroscopy, and the results are as follows: Figure 2 As shown, there are obvious characteristic peaks of phosphate ester groups and C=N, indicating that the material was successfully synthesized.

[0044] Example 2

[0045] S1: 7.0 g sodium hydroxide and 12.0 g urea were dissolved in 81.0 g water. 5.0 g cellulose powder was added to the above solution. The mixture was stirred vigorously in an ice-water bath, and then 5 g methacrylonitrile was slowly added. The reaction was carried out at room temperature for 10 hours under nitrogen protection. After the reaction was completed, acetic acid was added to adjust the pH to 7.0. The resulting white solid was filtered, washed, and freeze-dried to obtain cyanoethyl cellulose material.

[0046] S2: 2.0 g of cyanoethyl cellulose was dissolved in 198 g of N,N-dimethylformamide, then 2.4 g of hydroxylamine hydrochloride and 1.4 g of sodium hydroxide were added. The mixture was heated at 65°C for 14 hours. After the reaction was completed, the insoluble matter was removed by centrifugation. Then, a large amount of ethanol was added to the solution to form a precipitate. After filtration, washing with ethanol, and freeze drying, ceramide-oxime cellulose was obtained.

[0047] S3: 2.0 g of amylopyridine cellulose was dissolved in 198 g of N,N-dimethylformamide, and then 1.6 g of phosphorus oxychloride was added. The mixture was heated at 100°C for 5 hours. After the reaction was completed, it was cooled to room temperature. The white solid was filtered, washed with water, and freeze-dried to obtain a phosphate-amylopyridine synergistic functionalized cellulose adsorbent.

[0048] Example 3

[0049] S1: 7.0 g sodium hydroxide and 12.0 g urea were dissolved in 150.0 g water. 9.0 g cellulose powder was added to the above solution. The mixture was stirred vigorously in an ice-water bath, and then 9.0 g acrylonitrile was slowly added. The reaction was carried out at room temperature for 20 hours under nitrogen protection. After the reaction was completed, acetic acid was added to adjust the pH to 7.0. The resulting white solid was filtered, washed, and freeze-dried to obtain cyanoethyl cellulose material.

[0050] S2: 2.0 g of cyanoethyl cellulose was dissolved in 48 g of N,N-dimethylacetamide, then 2.4 g of hydroxylamine hydrochloride and 1.4 g of potassium hydroxide were added. The mixture was heated at 65°C for 20 hours. After the reaction was completed, the insoluble matter was removed by centrifugation. Then, a large amount of ethanol was added to the solution to form a precipitate. After filtration, washing with ethanol, and freeze drying, ceramide-oxime cellulose was obtained.

[0051] S3: 2.0 g of amylopyridine cellulose was dissolved in 48 g of N,N-dimethylformamide, and then 2.0 g of phosphorus pentoxide powder was added. The mixture was heated at 100°C for 5 hours. After the reaction was completed, it was cooled to room temperature. The white solid was filtered, washed with water, and freeze-dried to obtain a phosphate-amylopyridine synergistic functionalized cellulose adsorbent.

[0052] Example 4

[0053] S1: 7.0 g sodium hydroxide and 12.0 g urea were dissolved in 50.0 g water. 1.7 g cellulose powder was added to the above solution. The mixture was stirred vigorously in an ice-water bath, and then 3 g trans-butenedionitrile was slowly added. The reaction was carried out at room temperature for 8 hours under nitrogen protection. After the reaction was completed, acetic acid was added to adjust the pH to 7.0. The resulting white solid was filtered, washed, and freeze-dried to obtain cyanoethyl cellulose material.

[0054] S2: 2.0 g of cyanoethyl cellulose was dissolved in 48 g of dimethyl sulfoxide, then 2.4 g of hydroxylamine sulfate and 1.4 g of sodium hydroxide were added. The mixture was heated at 65°C for 15 hours. After the reaction was completed, the insoluble matter was removed by centrifugation. Then, a large amount of ethanol was added to the solution to form a precipitate. After filtration, washing with ethanol, and freeze drying, the amylopyroxycellulose was obtained.

[0055] S3: 2.0 g of amylopyridine cellulose was dissolved in 48 g of N,N-dimethylformamide, and then 2.0 g of phosphoric acid was added. The mixture was heated at 120°C for 2 hours. After the reaction was completed, it was cooled to room temperature. The white solid was filtered, washed with water, and freeze-dried to obtain a phosphate-amylopyridine synergistic functionalized cellulose adsorbent.

[0056] Example 5

[0057] The preparation method in this embodiment is the same as in Example 1, except that in this embodiment, in step S1, the nitrile compound is selected from 3-butenonitrile, the mass ratio of cellulose powder to nitrile compound is 1:1, the reaction temperature is 0℃, and the reaction time is 20 hours. In step S2, the hydroxylamine compound is hydroxylamine sulfate, the mass ratio of cyanoethyl cellulose, hydroxylamine compound, and alkali metal hydroxide is 2:1:10, the reaction temperature is 80℃, and the reaction time is 10 hours. In step S3, the mass ratio of geminal oxime cellulose to phosphorus-containing compound is 2:5, the reaction temperature is 120℃, and the reaction time is 1 hour.

[0058] Example 6

[0059] The preparation method in this embodiment is the same as in Example 1, except that in this embodiment, in step S1, the nitrile compound is selected from cis-butenedionitrile, the mass ratio of cellulose powder to nitrile compound is 1:2, the reaction temperature is 10°C, and the reaction time is 10 hours. In step S2, the hydroxylamine compound is hydroxylamine sulfate, the mass ratio of cyanoethyl cellulose, hydroxylamine compound, and alkali metal hydroxide is 2:5:10, the reaction temperature is 40°C, and the reaction time is 20 hours. In step S3, the mass ratio of geminal oxime cellulose to phosphorus-containing compound is 2:3, the reaction temperature is 80°C, and the reaction time is 5 hours.

[0060] Comparative Example 1 Step 1: Dissolve 7.0 g sodium hydroxide and 12.0 g urea in 100.0 g water, add 5.0 g cellulose powder to the above solution, stir vigorously in an ice-water bath, then slowly add 1.0 g acrylonitrile, react at room temperature for 8 hours under nitrogen protection, after the reaction is completed, add acetic acid to adjust the pH to 7.0, the resulting white solid is filtered, washed and freeze-dried to obtain cyanoethyl cellulose material.

[0061] Step 2: 2.0 g of cyanoethyl cellulose was dissolved in 80 g of N,N-dimethylformamide, and then 2.4 g of hydroxylamine hydrochloride and 1.4 g of sodium hydroxide were added. The mixture was heated at 65°C for 10 hours. After the reaction was completed, the insoluble matter was removed by centrifugation. Then, a large amount of ethanol was added to the solution to form a precipitate. After filtration, washing with ethanol, and freeze drying, the amylopyridine cellulose adsorbent was obtained.

[0062] Comparative Example 2 2.0 g of cellulose powder was dissolved in 80 g of N,N-dimethylformamide, and then 1.0 g of phosphorus pentoxide powder was added. The mixture was heated at 90°C for 1 hour. After the reaction was completed, it was cooled to room temperature. The white solid was filtered, washed with water, and freeze-dried to obtain phosphorylated cellulose adsorbent.

[0063] Application Example 1 Using the phosphate-enzyme-co-functionalized cellulose obtained in Example 1 as a sample, 13 equal portions (0.05 g each) were added to 50 mL of 100 mg·L⁻¹ solution. -1 In a uranium ion solution with pH=6.0, the cellulose was shaken for different times at 25℃, then removed, filtered, and the concentration of residual ions in the water was measured to calculate the adsorption capacity. Photos of the phosphate-mercapto-oxime co-functionalized cellulose before and after adsorption are shown below. Figure 3 As shown in the figure. The relationship between time and adsorption amount is shown in the figure. Figure 4 As shown in the figure, the adsorption equilibrium time for uranium ions is 60 minutes, and the equilibrium adsorption capacity is 94.6 mg·g⁻¹. -1 .

[0064] Application Example 2 Using the phosphate-enzyme-co-functionalized cellulose obtained in Example 2 as a sample, nine equal portions (0.05 g each) were added to 50 mL of 100 mg·L⁻¹ solution. -1 Uranium ion solutions with pH values ​​of 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, and 9.0 were shaken at 25°C for 60 minutes, filtered, and the concentration of residual ions in the water was measured to calculate the equilibrium adsorption capacity. The relationship between solution pH and uranium ion adsorption capacity is shown in the figure below. Figure 5 As shown in the figure, the adsorbent exhibits high adsorption capacity in the pH range of 3 to 9.

[0065] Application Example 3 0.05 g of the phosphate-enzyme-co-functionalized cellulose obtained in Example 3 was added to 50 mL of 100 mg·L⁻¹ cellulose. -1 In a uranium ion solution with pH=6.0, the mixture was shaken at 25℃ for 60 min, and the concentration of residual ions in the water was measured to calculate the removal rate. A 0.1 mol·L⁻¹ solution was used. -1 Sodium carbonate solution desorbs uranium ions from the adsorbent. The concentration of desorbed uranium ions is measured, and the desorption rate is calculated. The desorbed adsorbent is filtered, washed, freeze-dried, and then added back to the uranium ion solution for cyclic adsorption. This process is repeated 10 times, and the uranium ion removal rate and desorption rate are calculated for each cycle. The results are as follows: Figure 6As shown in the figure, after 10 cycles, the adsorbent still achieves a 76% removal rate for uranium ions and a 70% resolution rate.

[0066] Application Example 4 Using the amylopyridine cellulose obtained in Comparative Example 1 as a sample, 13 equal portions (0.05 g each) were added to 50 mL of 100 mg·L⁻¹ solution. -1 In a uranium ion solution with pH=6.0, the solution was shaken for different times at 25℃, then removed, filtered, and the concentration of residual ions in the water was measured to calculate the adsorption capacity. The relationship between time and adsorption capacity is shown in the graph below. Figure 7 As shown in the figure, the adsorption equilibrium time for uranium ions is 300 minutes, and the equilibrium adsorption capacity is 55.3 mg·g⁻¹. -1 .

[0067] Application Example 5 Using the phosphorylated cellulose obtained in Comparative Example 2 as a sample, 13 equal portions (0.05 g each) were added to 50 mL of 100 mg·L⁻¹ solution. -1 In a uranium ion solution with pH=6.0, the solution was shaken for different times at 25℃, then removed, filtered, and the concentration of residual ions in the water was measured to calculate the adsorption capacity. The relationship between time and adsorption capacity is shown in the graph below. Figure 8 As shown in the figure, the adsorption equilibrium time for uranium ions is 60 minutes, and the equilibrium adsorption capacity is 45.4 mg·g⁻¹. -1 .

[0068] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. A process for the preparation of phosphato-amidoxime synergistically functionalized cellulose adsorbent, characterized by, The method comprises the following steps: S1, dissolving cellulose powder in an alkaline aqueous solution of urea, stirring under ice water bath, then adding a nitrile compound, reacting under nitrogen protection, adjusting pH after the reaction is completed, then filtering, washing, and freeze-drying to obtain a cyanoethyl cellulose material; S2, dissolving the cyanoethyl cellulose material obtained in S1 in an organic solvent, adding a hydroxylamine compound and an alkali metal hydroxide, and heating to react, centrifuging to remove insoluble substances after the reaction is completed, adding ethanol to the solution to generate a precipitate, filtering, washing with ethanol, and freeze-drying to obtain an amidoxime-functionalized cellulose; S3, dissolving the amidoxime-functionalized cellulose in an organic solvent, then adding a phosphorus-containing compound, heating to react, cooling to room temperature after the reaction is completed, filtering, washing with water, and freeze-drying to obtain a phosphonic acid group-amidoxime group synergistically functionalized cellulose.

2. The preparation method according to claim 1, characterized in that, The nitrile compound is selected from one of acrylonitrile, methacrylonitrile, trans-butenedinitrile, cis-butenedinitrile, and 3-butenenitrile.

3. The preparation method according to claim 1, characterized in that, One or more of the following technical features is included: the mass ratio of cellulose powder to nitrile compound in step S1 is 5: (1-10); The reaction temperature in step S1 is 0-30°C, and the reaction time is 8-20 hours.

4. The preparation method according to claim 1, characterized in that, The hydroxylamine compound in step S2 is selected from one of hydroxylamine hydrochloride, hydroxylamine sulfate, O-methylhydroxylamine hydrochloride, and free hydroxylamine.

5. The preparation method according to claim 1, characterized in that, One or more of the following technical features is included: The mass ratio of cyanoethyl cellulose, hydroxylamine compound, and alkali metal hydroxide in step S2 is 2: (1-5): (1-10); The reaction temperature in step S2 is 40-80°C, and the reaction time is 10-20 hours.

6. The preparation method according to claim 1, characterized in that, The phosphorus-containing compound in step S3 is selected from one of phosphorus pentoxide, phosphoric acid, polyphosphoric acid, and phosphorus oxychloride.

7. The preparation method according to claim 1, characterized in that, The mass ratio of amidoxime-functionalized cellulose to phosphorus-containing compound in step S3 is 2: (1-5).

8. The method of claim 1, wherein the step of forming the first and second layers is performed by a method selected from the group consisting of: sputtering, evaporation, and chemical vapor deposition. The reaction temperature in step S3 is 80-120°C, and the reaction time is 1-5 hours.

9. The phosphonic acid group-amidoxime group synergistically functionalized cellulose adsorbent prepared by the preparation method of any one of claims 1 to 8.

10. The phosphonic acid group-amidoxime group synergistically functionalized cellulose adsorbent prepared by the preparation method of any one of claims 1 to 8, or the application of the phosphonic acid group-amidoxime group synergistically functionalized cellulose adsorbent of claim 9 in the field of adsorption and recovery of uranium in wastewater.